2019
DOI: 10.1007/s10668-019-00537-8
|View full text |Cite
|
Sign up to set email alerts
|

Common agricultural policy and sustainable management of areas with natural handicaps. The Veneto Region case study

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Nature B.V.. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided acknowledgement is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In the concluding remarks, the authors generalize the results and discuss the limitations of this study and future research directions. This study complements the existing research on the impact of the Common Agricultural Policy on rural sustainability [7][8][9][10][11] and enriches it with insights about the negative outcomes of the implementation of CAP measures on rural sustainability in Lithuania, a new EU Member State. Promoting and enhancing the sustainability of rural regions through assuring the economic viability of farms is one of the key objectives of the Common Agriculture Policy [12].…”
Section: Introductionmentioning
confidence: 67%
“…In the concluding remarks, the authors generalize the results and discuss the limitations of this study and future research directions. This study complements the existing research on the impact of the Common Agricultural Policy on rural sustainability [7][8][9][10][11] and enriches it with insights about the negative outcomes of the implementation of CAP measures on rural sustainability in Lithuania, a new EU Member State. Promoting and enhancing the sustainability of rural regions through assuring the economic viability of farms is one of the key objectives of the Common Agriculture Policy [12].…”
Section: Introductionmentioning
confidence: 67%
“…(30% lower yield at 700 m altitude compared to wheat cultivation at 500 m) (Kowalczyk et al 2014). A comparative study in Italy showed that the support of the 2. pillar goes to the plains of 66% and the mountainous area of 19%, which points out the gap between the plain-mountainous area (Zolin et al 2020). It concluded that the LFA support in Poland also encourages the employment of labour in the areas where the rural population intensively works in agriculture (Zawalinska et al 2013).…”
Section: Policy Scenarios Discussion and Resultsmentioning
confidence: 95%
“…There were three major groups of studies in this cluster. The first group examined the implementation of sustainable development goals (SDG) (Weerasooriya et al, 2021 ; Phillips, 2021 ; Udemba, 2022 ), and environmental conservation policies (Z. Wang et al, 2022 ; Zolin et al, 2020 ). The second group explored the adoption of a circular economy (di Vaio et al, 2023 ; Mirzaei & Shokouhyar, 2022 ; Rasool et al, 2022 ), environmental innovations (Tiwari & Thakur, 2021 ; Weimin et al, 2022 ).…”
Section: Results Of Bibliometric and Content Analysesmentioning
confidence: 99%